Quantification and Monitoring of the Effect of Botulinum Toxin A on Paretic Calf Muscles of Children With Cerebral Palsy With MRI: A Preliminary Study - Weidensteiner, Claudia; Madoerin, Philipp; Deligianni, Xeni; Haas, Tanja; Bieri, Oliver; Akinci D'Antonoli, Tugba; Bracht-Schweizer, Katrin; Romkes, Jacqueline; De Pieri, Enrico; Santini, Francesco; Rutz, Erich; Brunner, Reinald; et al. (Frontiers in Neurology, 2021)
Background: Muscles from patients with cerebral palsy (CP) are often spastic and form contractures that limit the range of motion. Injections of Botulinum toxin A (BTX) into the calf muscles are an important treatment for functional equinus; however, improvement in gait function is not always achieved. BTX is also used to test muscle weakening for risk evaluation of muscle lengthening surgery. Our aim was to assess the effect of BTX over time on calf muscle properties in pediatric CP patients with MRI. Material and Methods: Six toe-walking CP patients (mean age 11.6 years) with indication for lengthening surgery were prospectively enrolled and received BTX injections into the gastrocnemius and soleus muscles. MRI scans at 3T of the lower legs and clinical examinations were performed pre-BTX, 6 weeks (6w), and 12 weeks (12w) post-BTX. A fat-suppressed 2D multi spin-echo sequence was used to acquire T2 maps and for segmentation. Fat fraction maps were calculated from 3D multi-echo Dixon images. Diffusion tensor imaging (DTI) with a 2D EPI sequence yielded maps of the mean apparent diffusion coefficient (ADC) and of the fractional anisotropy (FA). Hyperintense regions of interest (ROI) on the T2-weighted (T2w) images at 6w were segmented in treated muscles. Mean values of T2, fat fraction, ADC, and FA were calculated in hyperintense ROIs and in reference ROIs in non-treated muscles. Results: Hyperintensity on T2w scans and increased T2 (group mean ± standard deviation: 35±1 ms pre-BTX, 45±2 ms at 6w, 44±2 ms at 12w) were observed in all patients at the injection sites. The T2 increase was spatially limited to parts of the injected muscles. FA increased (0.30±0.03 pre-BTX, 0.34±0.02 at 6w, 0.36±0.03 at 12w) while ADC did not change in hyperintense ROIs, indicating a BTX-induced increase in extracellular space and a simultaneous decrease of muscle fiber diameter. Fat fraction showed a trend for increase at 12w. Mean values in reference ROIs remained unchanged. Conclusion: MRI showed limited spatial distribution of the BTX-induced effects in pediatric CP patients. It could be a promising non-invasive tool for future studies to test BTX treatment protocols.